Self-discovery in Paulo Coelho’s Aleph (Journal of the College of Languages (JCL), 2018)
There is no doubt that complexities and ambiguities exist in the human minds. The need to unravel and solve those mysteries and the foggy actualities of life’s existence has been one of Paulo Coelho’s (1947-present) biggest concern. In almost all his novels, Coelho shows how people should dig deep into the mysteries of life in order to find a true understanding to their existence. In doing so, a true kind of enlightenment and purification is reached and the quest for self-discovery or self-realization is attained. The paper tackles one of Paulo Coelho’s novels Aleph (2011) which is considered as an autobiographical reading to signify the connection between himself and God. It was a phase that Coelho went through when he had actually achieved fame, wealth, and an understanding wife, yet the feeling of discomfort and that something was still missing kept haunting him. Thus, the train journey that he takes can be signified as his reconnection with his spiritual existence to achieve the desired self-discovery. The framework of this study is interpreted through the theories of spirituality and psychoanalytic to prove how the character experiences a higher level of spirituality in order to reach the desired realm of self- discovery.Coelho through the mouthpiece of his character spreads the message that in order to possess a comforting inner self, one should learn how to forgive and love others. Only then that a person’s true self-realization and satisfaction are attained.